SPECTROPOLARIMETRY OF β Cephei TYPE STAR γ Pegasi - Butkovskaya, V. V. (Одеські астрономічні публікації, 2017)
Results of an intensive spectropolarimetric study of the small-amplitude purely radial pulsating β Cephei- type star γ Pegasi are presented. It was shown that residual intensity, full width at half maximum and equivalent width of the He I 6678 line vary during 0.15-day pulsation period and reach its maximal value when the temperature of the star is highest. The line parameter variations due to pulsation were explained as a temperature effect. Although no strong signatures appear in the individual longitudinal magnetic field measurements, its probable coherent variation with the well-known 0.15-day pulsation period is an indication of the presence of a weak magnetic field in γ Pegasi. The values of γ -velocity and 2K- amplitude of the pulsation velocity curves are presented as well as the results of its variations due to the 6.83-day orbital period.